A new reliable numeric-analytic technique to solve nonlinear system of ordinary differential equations - Chowdhury, M. S. H. (2009)

(untitled)
In this paper, an analytical expression for the solution of the prey-predator problem by Modified homotopy-perturbation method (MHPM) is presented. The MHPM is treated as an algorithm for approximating the solution of the problem in a sequence of time intervals, \ie the classical HPM is converted into a hybrid numeric-analytic method called the multistage HPM (MHPM). Numerical comparisons with the classical HPM, and the classical fourth-order Rungge-Kutta (RK4) methods are presented. Numerical comparisons between the multistage homotopy-perturbation method (MHPM) and the classical fourth-order Runge-Kutta (RK4) numerical solutions reveal that the new technique is a promising tool for the nonlinear systems of ODEs.